Reciprocal relationships between job resources and work engagement in teachers: a longitudinal examination of cross-lagged and simultaneous effects - Uslukaya, Alper; Zincirli, Muhammed (Springer, 2025)
Although there is substantial evidence in the literature regarding the relationship between job resources and work engagement, the direction and timing of these relationships remain unclear. In this regard, the present study aimed to examine the time-lagged and concurrent reciprocal relationships between job resources and work engagement. To achieve this, a cross-lagged panel analysis with latent variables was conducted using data collected from 747 teachers over three waves. Findings revealed that previous job resources positively influenced subsequent work engagement, while prior work engagement also positively predicted later job resources. Additionally, when autoregressive and cross-lagged effects were controlled, job resources were found to have a concurrent positive impact on work engagement, whereas work engagement did not simultaneously affect job resources. Among the multiple models tested, the model demonstrating both time-lagged and concurrent reciprocal relationships between job resources and work engagement received the strongest empirical support. This result showed that the relationships between job resources and work engagement are best explained when all potential relationships are considered. Based on these results, the study offers several recommendations for policymakers, practitioners, and researchers.
Keywords: Job resources; Work engagement; Cross-lagged effects; Simultaneous effects